A prospective study of one-muscle surgery in 15–25 prism diopters horizontal comitant strabismus in adults - Apatsa Lekskul (2022)
Purpose: To prospectively evaluate the results of one-muscle surgery in 15–25 prism diopters (PD) horizontal comitant strabismus in adults. Patients and Methods: 15–25 PD horizontal strabismus patients, comprising 25 exotropic (XT) patients and 11 esotropic (ET) patients, who underwent one-muscle recession by a single surgeon with a fixed surgical dosage were included in the study with a minimum follow-up of 3 months. The main outcome was a surgical success, which is defined as a residual deviation of <8 PD at the last examination. Other parameters include postoperative lateral incomitance and patient satisfaction. Postoperative lateral incomitance indicated a difference in deviation of >5 PD between the primary position and lateral gaze, or duction limitation at any visit. Patient satisfaction regarding cosmetic and functional outcomes was assessed by using a 5-point Likert scale. Results: Successful alignment was obtained in 19 (76%) and 9 (81.81%) XT and ET patients (p = 1.00), with a median and interquartile range (IQR) of follow-up time of 3, 3–3 months and 3, 3–7 months, respectively. Postoperative lateral incomitance was observed in 8 (32%) XT patients and in 1 (9.09%) ET patient (p = 0.22). One XT patient and one ET patient who developed incomitance reported diplopia, which disappeared 3 months after surgery. One XT patient reported diplopia while gazing towards the operated eye whilst one ET patient reported diplopia occasionally which was unrelated to gaze direction. Patient satisfaction was based on Likert scale scores with 4.12 ± 0.97 in XT patients and 4.73 ± 0.65 in ET patients (p = 0.07). Conclusion: One-muscle recession with a fixed surgical dosage was effective for treating small angle horizontal strabismus with a high rate of surgical success and patient satisfaction. Although postoperative lateral incomitance occurred, only a few patients developed sympto-matic diplopia, which completely resolved 3 months after surgery.